Geopolitical shifts and intercommunal cooperation - The changes of geographical directions of international municipal cooperation in France, Germany and Poland. - Smutek, Jan (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri",sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: TR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="TR">The article describes geographical directions of the international cooperation of the municipalities of big cities in France, Germany and Poland. The study was conducted on the existing twinning agreements of the cities in the years 1945-2009. Particular attention was paid to the years 1980-2009. As a big city was recognized a city with the population above 100 thousand inhabitants in 2009. The political changes of 1989 in Europe, influenced the cooperation of the cities. While before 1989 the municipal international cooperation in Poland was rather small and limited to one side of the Iron Curtain, the end of the socialist system resulted in the rapid expansion of the international cooperation. That growth can be identified especially for Poland. The geographical directions of the cooperation of Polish cities changed and moved from East Europe and the so called neutral states to West Europe. At the end of the period of the analysis, the links with East Europe were reestablished in Poland. The cooperation in Germany was characterized by the existence of inter-German twin cities agreements. France is presented in the study as a comparison country. There are visible links with the Northern Africa countries. Cities from all the analyzed countries are establishing intercontinental partnerships, which could be understood as a sign of globalization.